A review of neurological health disparities in Peru - Faris Almubaslat; Sofia S. Sanchez-Boluarte; Monica M. Diaz (Frontiers in Public Health, 2023)
Peru is a historically unique and culturally diverse Latin American country. As a low-to-middle-income country (LMIC), Peru faces health implications from the spread of communicable diseases as well as a growing rate of noncommunicable diseases, both of which have been worsened by the recent COVID-19 pandemic’s impact on the national health system. Over the past two decades, the country has aimed to improve health access for its population through various efforts described in this review. Despite this, there are notable neurological health disparities that exist today. This narrative review investigates such disparities through the leading neurological contributors to the national burden of disease in the country, including migraine headaches, cerebrovascular disease, and dementia. Public health disparities that contribute to other major neurological diseases in the country, including epilepsy, neurocysticercosis, Chagas disease, multiple sclerosis, traumatic brain injury, traumatic and non-traumatic spinal cord injuries are also investigated. We also explore potential solutions for overcoming the various neurological health disparities covered in this review that may be applied through public policies, as well as in similar LMICs in Latin America. By overcoming such disparities, the country may be able to successfully address the major contributors of neurological disease burden and create a healthcare environment that can sustainably and equitably improve health outcomes for Peruvian people.